Hubungan kepatuhan bidan puskesmas dalam penerapan antenatal care terpadu berkualitas dengan deteksi komplikasi dan penyakit pada ibu hamil - Siti Sholikhah; Heru Pradjatmo; Mohammad Hakimi (Fakultas Kedokteran Universitas Gadjah Mada, 2016)
Compliance of midwife primary health center in implementation of the antenatal care integrated quality, disease detection and complications in pregnant womenPurpose This research aimed to determine the relationship of midwife’s compliance in the implementation of the antenatal care (ANC) integrated quality with disease detection and complications in pregnant women.MethodsThis research was an observational study with a retrospective cohort design. The sample was midwives who serve pregnant women in a primary health center, involving 125 midwives. The place of research was in 21 health centers throughout Kulon Progo. Research instruments used a questionnaire, with total sampling. Data analysis used: univariable analysis to determine the distribution of the data, bivariable with chi-square tests, multivariable with linear regression tests with 95% CI and significance of p=0.05, and a qualitative analysis.ResultsMidwives' compliance to the standard operating procedure has a 35% greater chance of detecting complications and illness in pregnant women than the midwife who did not follow standard operating procedure. Not all midwives in primary health care comply with ANC integrated quality.ConclusionThis study contributes to an understanding that compliance of midwives to ANC integrated quality is important as an effort to detect complications in pregnant women. The health office should establish a team for socialization, supervision, and assistance in the implementation of ANC integrated quality.